ANALISIS DISKRIMINAN SEKTOR EKONOMI PEMBENTUK KATEGORI INDEKS KAPASITAS FISKAL DAERAH (IKFD) PROPINSI DI INDONESIA - Budi Santoso (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The policies of a local government certainly have an impact on various aspects that exist in the area. Including the aspect of measuring regional fiscal capacity (RFC) as a measure of the ability of a region which is reflected through regional revenues minus revenues whose use has been determined and certain expenditures. The rise and fall of the regional fiscal capacity (RFC) of a province compared to other provinces can be caused by many factors, such as fiscal policy factors, natural resource wealth, and one of them is the economic sector performance factor in the province. Therefore, this study aims to determine the differences in RFC categories between provinces in Indonesia, find out what economic sectors can discriminate against RFC categories in provinces, in Indonesia, and determine the ability of the discriminant function in categorizing RFC provinces in Indonesia. The research method used is descriptive method in order to get an overview of the economic sector and fiscal capacity in all provinces in Indonesia. Then proceed with discriminant analysis to find out how the differences in RFC between provinces and which economic sectors can discriminate against RFC categories in provinces in Indonesia. The results showed that there were significant differences in the RFC category between provinces in Indonesia. The sectors that most determine the different categories of provincial RFC in Indonesia are wholesale and retail trade; car and motorcycle repair.